Monodisperse light color nanoparticle ink toward chromatic electrophoretic displays. Issue 21 (18th May 2016) - Peng, Bo; Li, Yue; Li, Jian; Bi, Lei; Lu, Haipeng; Xie, Jianliang; Ren, Xiangling; Cao, Yonghai; Wang, Ning; Meng, Xianwei; Deng, Longjiang; Guo, Zhanhu
Abstract : Lab-made monodisperse yellow, blue and pink nanoparticles with tunable sizes were tested as an ink to achieve chromatic electrophoretic displays. Abstract : The facile synthesis of nanoparticles for precise image control and fast response of chromatic electrophoretic displays (EPDs) is a challenge. Herein, we report a general method to prepare pink, blue, and yellow nanoparticles with low density and a tunable size of 230–310 nm. The monodispersity is down to 0.02 and surface charges are up to 666 e . Importantly, our work highlights the feasibility of chromatic nanoparticles as cost-effective candidates for electrophoretic displays.